2012
DOI: 10.1016/j.jand.2012.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Medical Nutrition Therapy: Methods to Improve Nutrition Provision in the Critical Care Setting

Abstract: Patients requiring mechanical ventilation in an intensive care unit commonly fail to attain enteral nutrition (EN) infusion goals. We conducted a cohort study to quantify and compare the percentage of energy and protein received between standard care (n=24) and intensive medical nutrition therapy (MNT) (n=25) participants; to assess the percentage of energy and protein received varied by nutritional status, and to identify barriers to EN provision. Intensive MNT entailed providing energy at 150% of estimated n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 36 publications
0
18
0
2
Order By: Relevance
“…Twelve studies recruited a heterogeneous group of patients, 8 , 20 , 21 , 23 , 26 33 3 studies recruited elderly patients, 34 36 2 studies each recruited post–liver transplant patients 37 , 38 and cardiac surgery patients, 7 , 22 and 1 recruited patients with acute kidney injury 39 . Fifteen articles 7 , 8 , 20 – 23 , 26 , 27 , 33 39 reported relevant clinical outcomes, of which 6 had low risk of bias 20 , 22 , 26 , 34 , 36 , 38 and were used to evaluate the association between malnutrition and ICU clinical outcomes (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twelve studies recruited a heterogeneous group of patients, 8 , 20 , 21 , 23 , 26 33 3 studies recruited elderly patients, 34 36 2 studies each recruited post–liver transplant patients 37 , 38 and cardiac surgery patients, 7 , 22 and 1 recruited patients with acute kidney injury 39 . Fifteen articles 7 , 8 , 20 – 23 , 26 , 27 , 33 39 reported relevant clinical outcomes, of which 6 had low risk of bias 20 , 22 , 26 , 34 , 36 , 38 and were used to evaluate the association between malnutrition and ICU clinical outcomes (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In approximately half of the studies, the clinician who carried out the nutrition screening and assessment was not identified * . Where this parameter was included, screening and assessment were performed by 1 or more dietitians in 5 studies, 21 , 27 , 28 , 32 , 34 physicians in 2 studies, 23 , 26 nurses in 1 study, 36 and a combination of physicians, nurses, and dietitians in the final study 8 . About 50% of the studies recruited predominantly patients from the medical ICU 8 , 20 , 23 , 26 , 27 , 31 35 and 1 study 39 from the surgical ICU.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To provide adequate EN, current studies are focused mostly on the choice of delivery timing, formula selection and route of administration [4]. Little attention has been paid to the potential contribution of EPI to malnutrition.…”
Section: Discussionmentioning
confidence: 99%